Complete Vision Loss following Orbital Cellulitis Secondary to Acute Dacryocystitis - Margaret L. Pfeiffer; Alexander Hacopian; Helen Merritt; Margaret E. Phillips; Karina Richani (Case Reports in Ophthalmological Medicine)
We present a case of a 50-year-old woman with acute dacryocystitis that was complicated by posterior rupture of the lacrimal sac causing an orbital cellulitis with subsequent visual acuity of no light perception. Upon presentation, she was immediately started on broad-spectrum antibiotics and underwent surgical incision and drainage of the lacrimal sac abscess but never regained vision. There are 4 cases in the literature of permanent severe vision loss from acute dacryocystitis. Prompt diagnosis and close monitoring of acute dacryocystitis are therefore essential to prevent extension into the orbit and possible optic nerve compromise.